Annika Tanner: capstone - Tanner, Annika, artist (Colorado State University. Libraries, 2026)
The artist's statement: My usage of shape and color creates a language to interrogate the transition from religious indoctrination to a spiritual desolation. Having been brought up in a Roman Catholic environment, I have been tied up in Christian beliefs and practices with just enough room to question what I was regurgitating, guiding me to abandon faith all together considering the hypocrisy and harm that brewed within the faith. The dynamic between my angular structures and fluid forms reflects the relationship between oil and water, two bodies that repel one another no matter how hard they try to integrate. My pieces combine stand-alone elements with one another to demonstrate the discrepancy between the two worlds I have found myself within. As I continue to navigate a path devoid of spiritual guidance, I find myself liberated from what I was told to believe and moving in a direction where I am working to define who I am and who I am meant to be independently.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing